Beta-lactam resistance pattern and sequence type in Portuguese Haemophilus influenzae invasive isolates - Frederico, Andreia Filipa Martins (2024)
Haemophilus influenzae is a human pathogen responsible for severe invasive disease such as meningitis, septicaemia, epiglottitis and pneumonia in children and adults. Beta-lactams antibiotics, such as ampicillin, are widely used as empirical treatment of these infections. The emergence of resistant strains, as a result of selective antibiotic pressure, has become an issue of concern. The aim of this study was to characterize the collection of 309 Haemophilus influenzae invasive isolates received between 2015 and 2021, in Haemophilus influenzae Reference Laboratory, from National Institute of Health Dr Ricardo Jorge, in Lisbon. Molecular characterization of ampicillin resistance mechanisms and genetic diversity was investigated to follow changes in epidemiology of Haemophilus influenzae invasive disease. Antimicrobial susceptibility was determined for 298 viable isolates, against 12 antibiotics. The ftsI gene, encoding the transpeptidase domain of penicillinbinding- protein 3, was sequenced for 74 isolates, both β-lactamase-producers and non-producers. Multilocus sequence typing was performed to examine genetic relatedness among 277 isolates. Previous characterization of capsular type showed that most isolates were nonencapsulated (72.8%) and 27.2% were encapsulated, with 12.3% serotype b, 7.8% serotype a, 4.8% serotype f and 2.3% serotype e. Overall, most isolates were susceptible to the antibiotics studied, with exception of 16.1% resistant to ampicillin and 21.1% resistant to trimethoprim-sulfamethoxazole. β-lactamaseproducers accounted for 13.3% of the isolates. Sequence analysis of ftsI gene, showed mutations in 70.3% of the isolates (52/74). Of the 74 isolates analysed, 52.7% were classified as genotypically β- lactamase-negative ampicillin-resistant and 8.1% as genotypically β-lactamasepositive ampicillin-clavulanic acid-resistant, according to their mutational patterns. Multilocus sequence typing revealed high genetic diversity among nonencapsulated isolates, while encapsulated isolates were clonal within each serotype. Two sequence types were predominant among nonencapsulated isolates, ST103 and ST1034, being associated, respectively, with β-lactamaseproducers and non-β-lactamase-producers. Our data reiterate the need for continued surveillance of resistance in Haemophilus influenzae infections, which will help to develop Public Health prevention strategies.